Effects of Extra Curricular Activities and Perceived Academic Self - Efficacy Among Grade 6 Pupils of Beti Elementary School - Sabado, Mary Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
Extracurricular activities (ECAs) are important in education worldwide because they help students grow in a well-rounded manner. This study took a closer look at how these activities affect the academic self-confidence of Grade 6 students at Beti Elementary School during the 2025–2026 school year. It specifically looked at the extent of students participation in these activities, their confidence in their academic abilities, and the connection between these two factors. The study used a descriptive-correlational research design and involved 50 randomly selected Grade 6 students. To gather data, a questionnaire created by the researcher and the standardized Morgan-Jinks Student Efficacy Scale (MJSES) were used. The data analysis involved statistical tools such as frequency counts, percentages, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient. The findings showed that the students were highly involved in extracurricular activities and had a strong sense of academic self-confidence, with an overall mean score of 3.24. Additionally, there was a significant moderate positive relationship between extracurricular activities and academic self-efficacy (r = 0.52, p = 0.000). This means that when students participate in extracurricular activities, their academic confidence tends to increase. The study concluded that extracurricular activities positively impact students’ academic self-confidence and support their overall development and motivation in academics.